Visuality and Slave Management in the Brazilian and Cuban Coffee and Sugar Plantations, c. 1840–1880 - de Bivar Marquese , Rafael (Comparativ, 2021)
The aim of the article is to understand how the new mechanisms of slave management developed in the Cuban and Brazilian sugar and coffee frontiers during the nineteenth century were connected to a new visuality of slavery. The argument is that it is possible to identify a cluster of new strategies aimed at extracting more labour from slaves in the coffee and sugar cane plantations of Brazil and Cuba, which was not only a response to the great reorganization of the world economy under industrial capitalism, but also to new patterns of slave resistance. These strategies can be understood as part of a new visual regime of New World slavery.